Potential impact of the Mineral and Petroleum Resources Development Amendment Bill on investment in South Africa's upstream oil and gas industry - Ellis, Maryke Louise (Department of Finance and Tax, 2015)
The Mineral and Petroleum Resources Development Amendment Bill has drawn criticism from industry experts and the press. There are a number of amendments that could be damaging to future investment in South Africa's upstream oil and gas industry. This study examines the key changes brought about by the Bill, South Africa's fiscal terms, how the fiscal terms are impacted by the Bill and current activity in South Africa's upstream oil and gas sector. The report then focuses on the most significant change made by the Bill, which is the level of State Participation. A fit for purpose economic model was built and the resulting cash flows were used to calculate the economic indicators presented in the results. The results from the model indicate how the increase in State Participation levels affects the ranking of South Africa's fiscal terms and the profitability of hypothetical investment opportunities. When ranked on fiscal terms, the country moves from having some of the best terms in Africa without the new Bill, to a position where the fiscal terms can be described as average or even onerous, depending on the interpretation of the State Participation clause. Accordingly, the result of the hypothetical investment opportunity has very positive economic indicators without the changes from the new Bill. If the most optimistic interpretation of the State Participation clause is modelled, the opportunity is less attractive but still viable and if the most pessimistic interpretation is modelled, the opportunity would not warrant investment. Even though South Africa has limited reserves, significant exploration activity is taking place under the existing legal and fiscal framework. If the Bill is implemented in its current format, it is likely that the country will see a significant decline in investment in the upstream oil and gas industry. Attracting new investment by international oil and gas companies in an environment governed by the terms of the proposed Bill will be challenging.